Pudendal Nerve Block by Low‐Frequency (≤1 kHz) Biphasic Electrical Stimulation. Issue 6 (6th August 2020) - Shapiro, Katherine; Guo, Wenbin; Armann, Kody; Pace, Natalie; Shen, Bing; Wang, Jicheng; Beckel, Jonathan; de Groat, William; Tai, Changfeng
Abstract: Objectives: To test the hypothesis that poststimulation block of nerve conduction can be achieved by low‐frequency (≤1 kHz) biphasic stimulation (LFBS). Materials and Methods: A tripolar cuff electrode was placed around the pudendal nerve in cats to deliver LFBS (1 kHz, 500 Hz, and 100 Hz). Two bipolar hook electrodes were placed central and distal to the cuff electrode to induce external urethral sphincter (EUS) contractions. A catheter was inserted into the urethra to record EUS contraction pressure. Pudendal nerve block by LFBS was confirmed by the failure of the central hook electrode stimulation to induce EUS contractions, while the distal hook electrode stimulation still induced contractions. Results: Pudendal nerve conduction was completely blocked by LFBS at different frequencies (1 kHz, 500 Hz, and 100 Hz) after terminating LFBS. The post‐LFBS block induced at the minimal stimulation intensity and duration was fully reversible within the same time period (10–15 min on average) for the three frequencies. However, the stimulation duration to induce block significantly ( p  < 0.05) increased from 23 ± 8 sec to 95 ± 14 sec when frequency increased from 100 Hz to 1 kHz. Conclusion: This study discovered that LFBS (≤1 kHz), like high‐frequency (≥5 kHz) biphasic stimulation (HFBS), can induce poststimulation block. The result provides support for the theory that biphasic stimulation waveforms block axonal conduction by changing intracellular and extracellular ion concentrations. The post‐LFBS block provides the opportunity to develop new neuromodulation devices for clinical applications where initial nerve firing is acceptable.